Himpunan Mahasiswa Pendidikan Fisika Mengabdi : Program Himafis Mengajar di Dusun Tojong-Ojong Sombek Desa Selebung Lombok Tengah - Rizky Munandar; Thufail Mujaddid Al-Qoyyim; Muhammad Abadi; I Wayan Gunada (Jurnal Pengabdian Magister Pendidikan IPA, 2021)
This activity aims to increase children's learning motivation during the pandemic through the play learning method. In addition, the Physics Education Student Association also carries out social activities such as community service and learning the Koran which is carried out at several points such as the Babussalam mosque which is located in the Tojong-Ojong Sombek hamlet, Selebung Village. This activity also aims to analyze the potential of play learning methods in increasing children's interest in learning in the midst of a pandemic and provide training on physics concepts in water rocket games.